Desconsideração da coisa julgada inconstitucional - Prado, Pedro Pierobon Costa do (2016)
The res judicata, as well as other institutes of procedural law, had their understanding changed with passage of time. Although it represents expression of legal certainty regarding lawsuits, as a Democratic State manifestation in judicial functions, intensive discussions about the possibility to relativize such institute are not recent, even without express statutory permission. The existence of a considerable number of precedents obtained by fraud, and others absurd, unjust, illegal and even unconstitutional means justify, according to legal experts, the positioning for withdrawal of res judicata protective mantle, in order to enable the case new discussion. On the other side, many are reticent about that, because preserving stability in legal and social relations. This study aims to examine arguments favorable and against, and the means available for claim preclusion disregard